Essential oils used in the poultry industry: Would it be an effective green alternative against Salmonella spp. dissemination and antimicrobial resistance? - Heitor Leocádio de Souza Rodrigues; Isis Mari Miyashiro Kolososki; Valdinete Pereira Benevides; Mauro M.S. Saraiva; Angelo Berchieri Junior (The Microbe)
Due to the increasing emergence of antimicrobial-resistant strains of Salmonella spp. isolated from poultry, and the global trend towards reducing antimicrobial use in food-producing animals, alternatives to these drugs are being sought. Among these alternatives, the antimicrobial action of essential oils (EOs) stands out. These compounds are plant-derived compounds with antimicrobial effectiveness against Gram-positive and Gram-negative bacteria, including strains of Salmonella. EOs are employed in the food industry due to their aromatic and antimicrobial properties and their role as natural preservatives as well. However, studies have been approaching their weight gain and performance instead of focusing on the applicability of these compounds in poultry challenged with avian salmonellae or other bacterial diseases. Therefore, the present study aimed to review the pros and cons of using EOs against Salmonella spp. in poultry. Although there are reports of the antimicrobial effectiveness of EOs against Salmonella spp. both in vitro and in vivo, their use for this purpose has not been deeply studied. Until then, optimal concentrations for controlling Salmonella shedding or toxic concentrations for poultry have not been established. On the other hand, it is known that these products can exhibit synergistic effects with other antimicrobials. Thus, investigations related to the pharmacokinetics, mechanisms of action, and adverse effects of EOs in the poultry's body are important to elucidate the treatment with these alternative antimicrobials, as well as to understand their interactions with both pathogenic bacteria and the bacteria that naturally compose the poultry's microbiota.